Evaluation of the Comprehensive Effects of Biodegradable Mulch Films on the Soil Hydrothermal Flux, Root Architecture, and Yield of Drip-Irrigated Rice - Zhiwen Song; Guodong Wang; Quanyou Hao; Xin Zhu; Qingyun Tang; Lei Zhao; Qifeng Wu; Yuxiang Li (Agronomy, 2025)
Biodegradable mulch films not only provide similar field benefits to conventional mulch films but also degrade naturally, rendering them an effective alternative to traditional polyethylene mulch films for mitigating “white pollution”. However, recent studies have focused on the material selection and soil ecological impacts of biodegradable mulch films, while their effects on soil water temperature regulation and root architecture in drip-irrigated rice cultivation remain unclear. To address this research gap, in this study, various treatments including no mulch (NM), conventional plastic mulch (PM), and four types of biodegradable mulch films (BM-W1, BM-B1, BM-B2, and BM-B3) were established, and their effects on the soil hydrothermal flux, root architecture, biomass accumulation, and resource use efficiency of drip-irrigated rice were analyzed at different growth stages. The results indicated the following: (1) Compared with the NM treatment, film mulching increased the soil hydrothermal fluxes and water retention capacity, thereby promoting root growth and biomass accumulation, ultimately increasing the effective panicle number and grain yield. (2) Among the biodegradable film treatments, BM-B3 (with a degradation period of 105 days) maintained relatively higher soil temperature for a longer duration, which increased surface root distribution in the mid-to-late growth stages, further improving fine root growth and biomass accumulation, consequently enhancing both yield and water use efficiency. In contrast, BM-B1 and BM-B2 exhibited excessively rapid degradation rates, leading to significant fluctuations in soil moisture and temperature, thereby negatively affecting water supply and nutrient uptake and ultimately restricting root growth and development. (3) The entropy weight (EW) technique for order of preference by similarity to ideal solution (TOPSIS) model results revealed that although the PM treatment was more advantageous in terms of soil temperature, root dry weight, and soil moisture content, BM-B3 provided a slightly higher yield than the PM treatment did and offered the advantage of biodegradability, making it a preferred alternative to conventional mulch film. In summary, this study revealed the mechanism by which biodegradable mulch films enhanced biomass accumulation and yield formation in drip-irrigated rice production by optimizing soil hydrothermal dynamics and root architecture, thereby exploring their potential as replacements for conventional mulch films. These findings provide a theoretical basis for the efficient and sustainable production of drip-irrigated rice in arid regions.